Innovative Strategies for Sustainable Tourism and Hospitality Growth in Indonesia (Editorial) - Subadra, I Nengah (Language Assistance, 2024)
Indonesia's tourism and hospitality industry is experiencing dynamic growth, necessitating innovative strategies to harness its full potential. This issue addresses key aspects crucial for sustainable and effective development. Topics include the potential of East Lombok's hotel industry, marketing strategies to boost occupancy at The Jayakarta Lombok Beach Resort, and destination marketing for Taman Mumbul in Sangeh. Sustainable tourism on Sumba Island is explored through cultural and natural resource utilization, while GIS-based approaches identify tourism potential in West Lombok's diverse landscapes. Additionally, enhancing teamwork through supervisory strategies at Bhira Restaurant, Denpasar, offers insights into improving service quality. These articles collectively provide strategic frameworks for increasing tourist engagement, supporting local economies, and promoting sustainability. The insights are designed to inspire research, collaboration, and practical implementation to strengthen Indonesia’s tourism sector in a competitive global market.